IMPLEMENTASI PROGRAM KAMPUNG KELUARGA HARAPAN (KB) DI DESA KARANGMANGU KECAMATAN PURWOJATI KABUPATEN BANYUMAS - Andri Trianfano; Suryoto Suryoto; Sartono Sartono (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
This research is entitled Implementation of the Familiy Planning Village Program in Karangmangu Vllage, Purwojati District, Banyumas Regency. The purpose of this study is to explain and describe the implementation of the Family Planning Village Program (KB) in Karangmangu Village. The research method used in this research is descriptive qualitative research method. To determine the informants in this study, it was done using a purposive teqnique, namely the informants who were deliberately selected by the researchers. The results of this study indicate that the communication that exists between the implementor and the target group is quite good, but still needs improvement in the coordination pattern, starting from reporting to evaluation. Then, the human resources that are owned are sufficient enough, but still needs to be done to improve the program facilities. The response and understanding of the implementer regarding the village family planning program is quite good. Keywords: Karangmangu, KB Village, Policy Implementation.